Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2022
DOI: 10.1002/tee.23566
|View full text |Cite
|
Sign up to set email alerts
|

Optimal Dispatching of Regional Interconnection Multi‐Microgrids Based on Multi‐Strategy Improved Whale Optimization Algorithm

Abstract: The interconnection of multiple microgrids can effectively improve the operating efficiency of the system and reduce the cost of power generation. First, establish an economic environment optimal dispatch model based on the regional interconnected multi‐microgrids system, and formulate a dispatch strategy based on the time‐of‐use electricity price and the supply‐demand relationship between microgrids; Secondly, in order to solve this constrained optimization problem, a whale algorithm improved with five strate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 14 publications
0
4
0
Order By: Relevance
“…Simulation results showed that the proposed algorithm applied to the model can effectively improve these objectives. Wang et al [17] established an economic dispatch model based on regional interconnected multi-microgrid systems, and proposed an improved whale algorithm using five strategies, namely adaptive inertia weight, dynamic spiral search and generalized binary learning, to solve this problem. The improved algorithm was applied to two arithmetic models of the grid-connected operation and non-grid-connected operation for testing, and it was found that the convergence accuracy and speed of the algorithm have been improved and the results obtained were good.…”
Section: Intelligent Optimization Algorithmmentioning
confidence: 99%
“…Simulation results showed that the proposed algorithm applied to the model can effectively improve these objectives. Wang et al [17] established an economic dispatch model based on regional interconnected multi-microgrid systems, and proposed an improved whale algorithm using five strategies, namely adaptive inertia weight, dynamic spiral search and generalized binary learning, to solve this problem. The improved algorithm was applied to two arithmetic models of the grid-connected operation and non-grid-connected operation for testing, and it was found that the convergence accuracy and speed of the algorithm have been improved and the results obtained were good.…”
Section: Intelligent Optimization Algorithmmentioning
confidence: 99%
“…The BFO integrated with various optimization parts has the highest search accuracy and the fastest iteration speed. This paper also compares some other algorithms for BFO optimization, such as the Hormone Regulation based Emotional Bacterial Foraging Algorithm (HR-EBFA) [ 41 ], Bacterial Foraging reinforcement Learning Optimization Algorithm (RL-BFA) [ 42 ], the improved Quantum Bacterial Foraging Algorithm (MQBFA) [ 44 ], and Distribution Estimation based adaptive Bacterial Foraging Algorithm (BFOED) [ 43 ]. The improved bacterial foraging algorithm presented in this paper has better results than the above methods.…”
Section: An Improved Bacterial Foraging Optimization and Its Applicationmentioning
confidence: 99%
“…However, the paper did not intuitively display the power distribution diagram of each unit. Wang et al [ 17 ] used a joint dispatch to solve the optimal dispatch problem of microgrids, but joint dispatch in multiple areas sacrifices the benefits of a single model, and the whale algorithm cannot balance this process well. Zhang Y et al use the butterfly algorithm to optimize microgrids [ 18 ].…”
Section: Introductionmentioning
confidence: 99%